Dialogic civility in a cynical age : community, hope, and interpersonal relationships - Arnett, Ronald C., 1952- (SUNY series in communication studies., 1999)
"Dialogic Civility in a Cynical Age offers a philosophical and pragmatic response to unreflective cynicism. Considering that each of us has faced inappropriate cynical communication in families, educational institutions, and the workplace, this book offers insight and practical guidance for people interested in improving their interpersonal relationships in an age of rampant cynicism."--Jacket